Mobile Support for Face-to-Face Social Interaction - Teevan, Jaime; Morris, Meredith Ringel; Saponas, Scott (2014 Human-Computer Interaction Consortium Workshop (HCIC), 2014)
Despite the fact that successful social applications tend to support strong social relationships, there are few mobile solutions that support strong co-located relationships. We call on the HCIC community to help address this gap by building mobile tools that augment people’s existing face-to-face interactions. We proposed several ways that mobile devices might be improved to help users engage with the people around them, rather than ignore their immediate social context. Mobile device use by co-located users is unique in that users share persistent verbal and non-verbal non-mediated communication channels and significant background context. Co-located mobile applications can take advantage of these unique aspects to support social interaction. Using several examples, we show that it is possible for mobile devices to not take their users’ attention away from the people they are with, and to augment existing physical and verbal communication. We are interested in engaging the HCIC community to brainstorm additional unique aspects of co-located social mobile device use, and to think about how these aspects might further be capitalized on to improve the social mobile experience. Our ultimate goal is for people to react positively when the person they are with pulls out a mobile device, rather negatively.